Esophageal Dieulafoy's lesion: an exceedingly rare cause of massive upper GI bleeding - Malliaras, George P. (J Surg Case Rep, 2016)
Dieulafoy's lesion, a dilated aberrant submucosal vessel which erodes the overlying epithelium, is a relatively rare but potentially fatal cause of gastrointestinal (Gl) bleeding. The esophagus is a very rare location for the lesion. Here we present a case of massive upper GI bleeding, secondary to this remarkably rare occurrence, which was amendable to endoscopic intervention.